Mesenchymal Stem Cell-Educated Macrophages Ameliorate LPS-Induced Systemic Response - Yaoqin Hu; Chaojin Qin; Guoping Zheng; Dengming Lai; Huikang Tao; Yan Zhang; Guanguan Qiu; Menghua Ge; Lanfang Huang; Lina Chen; Baoli Cheng; Qiang Shu; et al. (Mediators of Inflammation)
Both bone marrow and adipose-derived mesenchymal stem cells (ASCs) have immunomodulatory effects. The goal of this study was to determine whether ASCs-educated macrophages could directly ameliorate LPS-induced systemic response in a mouse model. Mouse peritoneal macrophages were cocultured with ASCs in a Transwell system for 2 days to educate macrophages. Mice were divided into 5 groups: control, LPS, LPS + ASCs, LPS + untreated macrophages, and LPS + educated macrophages. Educated macrophages decreased lung inflammation, weight loss, pulmonary edema, and inflammatory cytokine response. In vitro, ASCs increased expression of M2 macrophages independent of direct cell-to-cell contact when macrophages were treated with LPS or serum from patients with acute respiratory distress syndrome (ARDS). When macrophages were cultured with serum from ARDS patients who were treated with ASCs or placebo in our previous clinical trial, there was no difference in M2 macrophage levels before and after ASCs treatment indicating a suboptimal response to the treatment protocol. ASCs also reduced the levels of LPS-induced proinflammatory cytokines in vitro which were mimicked by IL-10 and blocked by antibodies for IL-10 and IL-10 receptor supporting the notion that educated macrophages exert their anti-inflammatory effects via IL-10-dependent mechanisms.